Rewriting belonging: Postcolonial identity, diasporic memory, and power in contemporary English literature - Khan, Aayesha Sagir; Saleh, Shoeb; AlAli, Rommel Mahmoud; Abdullatif, Ali (Research Journal in Advanced Humanities, 2026)
Contemporary Anglophone postcolonial fiction repeatedly returns to the language of home, migration, return, and affiliation, yet it rarely treats belonging as a stable possession. This essay argues that in Mohsin Hamid’s Exit West, Kamila Shamsie’s Home Fire, Chimamanda Ngozi Adichie’s Americanah, and Bernardine Evaristo’s Girl, Woman, Other, belonging is rewritten as a struggle over narrative authority rather than a recovered attachment to place. These novels relocate the question of who belongs from the idioms of origin and assimilation to scenes of border control, racial legibility, familial memory, public mourning, and collective narration. Drawing on postcolonial theory, diaspora studies, and memory studies, the essay shows that diasporic memory in these texts is not private nostalgia but a mode of transmission through which states, publics, and families decide which lives appear intelligible, grievable, and proximate. Hamid’s portals expose the distributed infrastructures of the global border regime; Shamsie’s tragic design converts citizenship into a contest over mourning and burial; Adichie’s return narrative turns racial memory into a transformed relation to home; and Evaristo’s polyphony rewrites the national story from the vantage point of black British women’s interlinked lives. Read together, these novels make a sharper claim than the language of mobility alone can capture: belonging is not where one finally arrives, but the unstable social relation produced when memory, power, and narration meet.